Joseph Schacht dan Konsep Awal Pembentukan Hukum Islam ‘’Kajian Atas Perspektif Orientalis’’ - Siti Khadijah; Anwar Hafidzi (Interdisciplinary Explorations in Research Journal, 2024)
This article discusses the initial concept of the formation of Islamic law according to Joseph Schacht, a German-British orientalist. Schacht argued that Islamic law was formed through the interaction of religion, culture, and politics. This study will analyze Schacht's perspective and its impact on the understanding of modern Islamic law. Furthermore, the article will also critique the weaknesses of Schacht’s approach and offer alternative perspectives for understanding the complexity of Islamic law. Schacht and his Contribution to Islamic Law: The author attempts to examine the thoughts of Joseph Schacht, which are then outlined in the research questions: What are Joseph Schacht’s ideas, and what is his contribution to Islamic law? In this study, the author employs a descriptive research method with Shari’a, historical, and philosophical approaches, using library research as the data collection method. The data collection techniques used in this research are deductive and comparative methods, while data analysis is conducted using qualitative descriptive analysis. The objective of this thesis is to explore the thoughts of Joseph Schacht, an orientalist, on Islamic law and the contribution of his ideas to Islamic law. The findings of this study show that Joseph Schacht, as an orientalist, analyzed Islamic law through historical-sociological research. In this context, Schacht attempted to address multiple aspects of Islamic law. He presented Islam not as a set of divinely revealed norms but as a historical phenomenon closely tied to its social setting, meaning he studied the authenticity of Islamic law sources through historical processes. Joseph Schacht also did not acknowledge hadith as a source of Islamic law. His research, presented in his works, became a reference for legal scholars discussing Islamic law, especially for Westerners who were not fully familiar with Islamic law. However, his rejection of hadith as a source of Islamic law had a significant impact on Islamic law. This led to considerable doubt about the strength and authenticity of Islamic law, not only among the Western world but also among Muslims themselves.